KARYA KOMPOSISI MUSIK TETEG, REINTEPRETASI TRADISI PATHETAN SLENDRO SANGA NGELIK - Fatimah, Mutiara Dewi (Sorai: Jurnal Pengkajian dan Penciptaan Musik, 2018)
ABSTRACTÂ The word â€œtetegâ€ comes from the Java language which means dare to deal with all issues both physical and non-physical. Teteg has the same synonym with tatag, tangguh, tanggon, and teguh. The form of this musical work is a reinterpretation of the traditional repertoire into a musical composition with new forms and colors. With the method of developing the traditional source, the composer carries the tradition of pathetan Sanga Ngelik. Pathetan sanga ngelik as the source of the creation of this music will be processed with a â€œgarapâ€ approach. One of the elements of garap mentioned above includes: technique, pattern, rhythm, laya, laras, pathet, and dynamics. Pathetan sanga ngelik will be described into several forms such as, merong form, ladrang, ketawang, lancaran, ayak-syak, srepeg, and palaran. This music also explores various characters which is called "rasagendhing" that consists : rasa sereng, gagah, regu, prenes, sigrak, gumyak, luruh, and gayeng or gecul. In this part, drama and music concepts appear in this work. Some other styles also exist in this work, among others: this work combines Surakarta style (Solo), Yogyakarta style, Nartosabdan style and also style outside the palace (rural) or Sragenan. The idea of this art work will be framed by the concept of "teteg" with meaning contained.Â Kata kunci: komposisi musik, teteg, reintepretasi tradisi pathetan slendro sanga ngelikÂ